ETIKA BELAJAR DALAM AL-QURAN: (Studi Analisis Surat Al-Kahfi Ayat 66-78) - Muzakki, Zubairi; Illahi, Nur; Muljawan, Asep (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2022)
Rasulullah SAW in spreading the teachings of Islam is full of gentleness, what he conveys is always a good example for his people. He is a successful leader in leading and spreading the understanding of the Islamic religion, so that all mankind can follow what he teaches. Likewise, when the prophet Khidr taught sciences that were not understood by the prophet Moses. Likewise, the prophet Moses can also be a lesson for all of us to seek knowledge. Ethics is very important for every student of knowledge as Allah has immortalized in Surah al-Kahf verses 66-78. The author tries to research and describe "Ethics in Learning in the Al-Quran" with the hope that we can be successful in studying so that the knowledge we demand can be practiced and benefited all mankind. Because knowledge is like a lamp that always illuminates our every path, without knowledge humans will always be trapped in ignorance and disobedience. Therefore, the author tries to describe in detail how we seek knowledge so that the knowledge we learn can reach us who study it and can be useful for all. There are so many lessons that we can take from the meeting between the prophet Khidir and the prophet Musa, the most prominent thing is ethics in learning. Ethics in learning is very important, when a teacher has not explained it is better for us to be silent and follow the lesson well. Teachers have their own methods of educating their students.